The Use of the PIECES Method to Measure User Satisfaction with Higher Education Academic Portals in South Tangerang City - Tafsiruddin, M; Saefullah, Aep; Ismail, Zakki (International Journal of Research in Education, 2025)
This study aims to explore the use of the PIECES Method in measuring user satisfaction with academic portals at higher education institutions in South Tangerang City. User satisfaction with academic portals is crucial in enhancing efficiency, service quality, and learning experiences in a higher education environment. The study was conducted over eight months, from February to September 2024, across four higher education institutions in South Tangerang City. Data collection techniques included literature review, interviews, observations, and Focus Group Discussions (FGD). The findings of this research are expected to serve as a guide for higher education institutions in improving the quality of their academic portal services, thereby enhancing user satisfaction and learning experiences. The results indicate that the academic portals have met user expectations based on the PIECES framework. In terms of performance, the portal was rated as fast and stable, although it encountered challenges during high traffic periods, and e-learning features require further development. The information provided is accurate and up-to-date, while cost and time efficiency are considered good. Users feel they have adequate control over their data, and support services are viewed as responsive. These findings have significant implications for the management and development of academic portals, encouraging service quality improvements and ensuring the effective use of portals in higher education institutions.